(3eWdY GdHOhQ heLeY GdHMhQs - (3CMeO Hf UGdM Hf eMeO GHf CHi GdQLGd, Uaj GdOjf,J (B1092 (3g` s ((3MehO Hf eMeO Hf Ydi s)
(3ChdgG (B:s
(3GdMeOd dg GdPi LYd YdeGA GdYJQI ddMb YdeGA s
(3BNQgG (B:s
(3BNQg JQLeI GdYdGeI jhSa GdfYeGf , ef eYGUQi GdEeGe UdGM Hf Ydi Ydjg GdSdGe s
(3GdfSNI ai CQHYI CLRGA VegG eLdOGf hbO aQZ ef fSN GdeLdO GdChd SfI (B1342s
(3hGdKGfi SfI (B1343(3g` hai Chd GdfSNI JQLeI ddeDda hKHJ HCSeGA GdeJQLejfs
(3hcJHJ QDhS GdJQGLe HGdMeQIs
(3ai JQGLe GdRjOjI s
(3bQf GdfSN (B:s
(3GdbQf GdQGHY YTQs
Keywords: (3GdJGQjNs